Original paperComparison of detection of Borrelia burgdorferi DNA and anti-Borrelia burgdorferi antibodies in patients with erythema migrans in north-eastern Poland - Moniuszko, Anna; Dunaj, Justyna; Zajkowska, Joanna; Czupryna, Piotr; Świerzbińska, Renata; Guziejko, Katarzyna; Aleksiejczuk, Piotr; Barry, Gerald; Kondrusik, Maciej; Pancewicz, Sławomir (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Diagnostic methods in erythema migrans are still not standardized. Aim: To evaluate the frequency of Borrelia burgdorferi s.l. DNA presence in patients with erythema migrans (EM); to assess the polymerase chain reaction (PCR) procedure for detecting B. burgdorferi s.l. DNA in patients with the skin form of Lyme borreliosis; and to compare the results of the PCR-based method with the traditional ELISA method. Material and methods : Skin biopsy and blood samples from 93 patients with EM were examined for B. burgdorferi s.l. DNA detection (PCR). Seventy-one of these patients were examined for the presence of anti- B. burgdorferi s.l. antibodies (ELISA). Results : Borrelia burgdorferi s.l. DNA was detected in 48% of the skin biopsy specimens and in 2% of blood samples. Only 1 patient was PCR positive in both blood and skin samples. Seventy percent of patients whose PCR results were positive were bitten by a tick less than 14 days before. IgM anti- B. burgdorferi s.l – specific antibodies were present in the serum of 35% of patients and IgG antibodies – in 30% of patients. Seventeen percent were positive in both IgM and IgG. Conclusions : Polymerase chain reaction of skin biopsy specimens seems to be currently the most sensitive and specific test for the diagnosis of patients with EM, especially in patients with a short duration of the disease (< 14 days) but still its effectiveness is much lower than expected. Polymerase chain reaction of blood samples cannot be recommended at the present time for the routine diagnostic of patients with EM.